A New Optimization Approach for a Solar Tracker Based on an Inertial Measurement Unit - Rezoug, M. R.; Benaouadj, M.; Taibi, D.; Chenni, R. (Engineering, Technology & Applied Science Research, 2021)
Improvements and applications of Inertial Measurement Unit (IMU) sensors have increased in several areas. They are generally used in equipment that measures orientation, gravitational force, and speed. Therefore, in this paper, we worked on improving the performance of IMU in an application on solar trackers of the Kalman filter. This work illustrates the design of an autonomous device with astronomical control of a photovoltaic (PV) panel, allowing the optimization of the orientation/energy gain ratio. The device is based on two concepts at the same time, the modeling of the solar trajectory adopted by an algorithm which calculates continuously the solar angles (elevation and azimuth) and the approval of these by the IMU in order to sweep away any climatic fluctuations and thus allow an almost perfect adjustment relative to the perpendicular axis of the rays. The tracking system is based on two joints controlled by an Arduino control board. Experiments have shown a better performance of the two-axis device: the net energy gains can be around 34% with an additional 1.1% when the Kalman filter is applied.